Search for the Standard Model Higgs Boson in Tau Final States - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Sawyer, L.; et al. (Amer Physical Soc, 2009)
We present a search for the standard model Higgs boson using hadronically decaying tau leptons, in 1 fb(-1) of data collected with the D0 detector at the Fermilab Tevatron pp collider. We select two final states: tau(+/-) plus missing transverse energy and b jets, and tau(+)tau(-) plus jets. These final states are sensitive to a combination of associated W/Z boson plus Higgs boson, vector boson fusion, and gluon-gluon fusion production processes. The observed ratio of the combined limit on the Higgs production cross section at the 95% C.L. to the standard model expectation is 29 for a Higgs boson mass of 115 GeV.